2016
DOI: 10.1002/casp.2279
|View full text |Cite
|
Sign up to set email alerts
|

Solidarity and Reciprocity Between People With and Without Disabilities

Abstract: Governments of contemporary welfare states call upon citizens to care for people with psychiatric or intellectual disabilities. This is deemed sensible and morally just. However, social–psychological theory suggests that stereotyping may stand in the way of engaging into contact. Sociological theory suggests that the giving of help is based on either balanced or generalized reciprocity. Balanced reciprocity depends on one's ability to ‘pay back’, which people with disabilities may have trouble doing. Generaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Various studies in western countries show that people try to live up to the norm of the specific relationship (Bredewold, Tonkens, & Trappenburg, 2016;Ekeh, 1974;Komter, 2007;Uehara, 1990Uehara, , 1995.…”
Section: What This Paper Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies in western countries show that people try to live up to the norm of the specific relationship (Bredewold, Tonkens, & Trappenburg, 2016;Ekeh, 1974;Komter, 2007;Uehara, 1990Uehara, , 1995.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Various studies in western countries show that people try to live up to the norm of the specific relationship (Bredewold, Tonkens, & Trappenburg, ; Ekeh, ; Komter, ; Uehara, , ). These studies indicate that people find it difficult to ask for help, regardless of how desperately they need it.…”
Section: Introductionmentioning
confidence: 99%
“…Our research found that most citizens without intellectual disabilities (two-thirds of the group we examined) have no contact at all with people who have an intellectual disability. Where the two groups do meet, these tend to be superficial contacts in the street, during which they greet one another and chat (for these outcomes, see Bredewold et al, 2016aBredewold et al, , 2016b). An important reason for the failure to initiate contact is the struggle with difference.…”
Section: Resultsmentioning
confidence: 99%
“…In this section, we explain how our project was designed methodologically (the methods have been described before; see Bredewold et al, 2016aBredewold et al, , 2016b. This study was conducted between January and December 2012, in two neighbourhoods in the medium-sized city of Zwolle in the Netherlands.…”
Section: Study Design and Contextmentioning
confidence: 99%
See 1 more Smart Citation